'Shaking up' neoliberal policy in schools: Looking for democratic alternatives in Jacinta's satchel. Issue 4 (December 2018) - Robinson, Janean; Down, Barry; Smyth, John
Our research is driven by a strong belief that the stories of young people gathered through ethnographic interviews can generate awareness not only of the complexities, uncertainties and possibilities of young people's lives but also the ways in which their identities and life chances are shaped by broader structural, institutional and historical forces beyond their control. In this article, we introduce Jacinta, a young person who describes the events and conditions which serve to hinder and/or support her journey in school and beyond. We have used Jacinta's story from a larger research project, to speak back to the impact the broader neoliberalising agenda is having on young lives with a view to reimagining democratic alternatives in education.